The Power of Religiosity in Homosexual Adolescents: A Fenomenology Study in North Sumatra - Lodiana Ayu; Fadhilla Fajrah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The aim of this research is to examine the religiosity of homosexual teenagers in North Sumatra. This research is qualitative, with a phenomenological research design. Data collection was carried out using interview and observation techniques. Interviews were conducted in depth with homosexual teenagers by developing several questions to reveal five dimensions of religiosity. The research subjects were seven homosexual teenagers. The results of the research show that the religiosity of homosexual teenagers is categorized as good, except for the dimensions of appreciation and practice as well as the dimensions of experience that influence their behavior. Factors that influence the religiosity of homosexual teenagers include an incorrect understanding of religious concepts and a family environment that pays little attention to the appreciation and practice of their religion. The role of religious education in the family is to increase the religiosity of homosexual teenagers. Disputes regarding religion have a big influence on the subject. Feelings of sin and guilt towards religious teachings give rise to doubts about the internalization of religious teachings.